Santé et sécurité du travail et formation professionnelle : Prochaine cible d’intérêt - Serge André Girard; Pierrette Doyon; Louis Gilbert; Michel Legris; Denis Laliberté (Perspectives Interdisciplinaires sur le Travail et la Santé)
This study investigates the accident events associated with an injury, without considering its severity, that occurred during vocational training, as well as the typical symptoms of the students’ occupational exposure. In the participating school, 327 students are enrolled in the motorized equipment maintenance program. All the accident events that occurred during the 2003 fall session were documented, and 213 students completed a questionnaire on the symptoms related to occupational exposure in a training workshop. Between September and December 2003, 72 accident events were documented (accident event rate of 22%). Of these, 83.4% occurred in automotive mechanics and body repair. These specialties accounted for 62.9% of the enrolled students. However, the heavy truck mechanics and heavy construction vehicle specialties accounted for 16.3% of the accident events while representing 37% of the population under study. The symptom questionnaire revealed that 11.3% of the respondents had low back pain and 16.0% had skin problems that they mainly attributed to their exposure in a vocational workshop. Finally, 29.6% reported that they regularly felt tired, had difficulty concentrating or had headaches. The results provide important indications about the situation prevailing in the participating professional school. Management and teachers from this vocational establishment can identify risky activities and hazardous products, as well as propose the appropriate preventive measures. Although the exploratory nature of the study prevents any generalization to all other vocational workshops, it highlights the importance of documenting the occupational health and safety question in vocational training environments.